2013
DOI: 10.11594/jtls.03.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cadmium Uptake of Rice Plants Using Soil Amendments in High Cadmium Contaminated Soil: A Pot Experiment

Abstract: The aims of this study were to investigate the effect of agricultural residues on reducing cadmium uptake in rice plants. The rice plants growing on no cadmium/free cadmium soils (N), Cd soils (Cds), and Cd soils each amended with 1% w/w of coir pith (CP), coir pith modified with sodium hydroxide (CPm) and corncob (CC) under high cadmium contaminated soil with an average 145 mg Cd kg -1 soil were investigated. The results showed that the cumulative transpiration of rice grown in various treatments under high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Finally, 50.0 mg/L is the predicted possible concentration of BPA contained in soil in the future based on current rates of release into the environment, or the amount of BPA in soils suddenly polluted by high concentrations of BPA . In addition, the Cd concentration in soils reportedly varies between 0.01 mg/L and 3.37 mg/L . Moreover, 10.0 mg/L is the predicted possible concentration of Cd accumulated in soils in the future or the concentration of Cd in soils suddenly polluted by high concentrations of Cd .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 50.0 mg/L is the predicted possible concentration of BPA contained in soil in the future based on current rates of release into the environment, or the amount of BPA in soils suddenly polluted by high concentrations of BPA . In addition, the Cd concentration in soils reportedly varies between 0.01 mg/L and 3.37 mg/L . Moreover, 10.0 mg/L is the predicted possible concentration of Cd accumulated in soils in the future or the concentration of Cd in soils suddenly polluted by high concentrations of Cd .…”
Section: Methodsmentioning
confidence: 99%
“…Siswanto et al reported that the degradation of rice residues resulted in the production of high and low molecular organic acids. For instance, the presence of high molecular weight compound like humic acid in the residues decreased the uptake of Cd in the roots on the base of free Cd ion activity and total Cd concentration, whereas low molecular organic acids like citric acid increased the uptake and internalization of Cd .…”
Section: Bioavailability Of Ptes In Contaminated Soilsmentioning
confidence: 99%
“…The concentrations of BPA were designed to reflect those used in earlier investigations of the effect of BPA on terrestrial plants , current BPA pollution level records, developing trends of BPA contamination in the environment, and a hypothetical large accidental release into the environment, and are similar to those selected (1.5 mg/kg, 17.2 mg/kg, 50.0 mg/kg) by Sun et al . The Cd concentrations selected (0.2 mg/kg, 3.0 mg/kg) reflect reported levels in soils, which vary between 0.01 mg/kg and 3.37 mg/kg , and a higher (10.0 mg/kg) concentration that simulates a potential concentration of Cd accumulated in soils in the future or the concentration of BPA in soils suddenly polluted by Cd at high concentration .…”
Section: Methodsmentioning
confidence: 99%